HOUSING ECONOMY: USE OF INTERLOCKING MASONRY FOR LOW-COST STUDENT HOUSING IN NIGERIA - Y.M.D AYODEJI (Journal of Construction Project Management and Innovation)
This paper examines the overriding benefits of interlocking masonry over the conventional types in housing delivery in Nigeria. The study summarises and interprets the findings from an empirical survey of students’ housing projects in selected institutions in South-western Nigeria and Abuja, the capital city of Nigeria through case studies, interview schedules, and observations. Professionals like architects, engineers, quantity surveyors and building contractors involved in the designs and supervision of these projects were interviewed to obtain their views on the subject. Research variables investigated include: size of buildings; number of labourers engaged in masonry works; cost of masonry works; curing and setting time for concrete blocks; productive hours of labourers employed; and willingness to use these materials. Some selected buildings observed in the field that have been constructed using mortarless masonry construction systems are presented next. Data obtained from the field through observations and interview schedules were analysed and compared with both descriptive and inferential statistics. Analysis of results revealed the following: a high preference of professionals for the use of interlocking masonry over the conventional methods; faster construction time; labour and material cost savings with interlocking blocks. The limitations of the use of interlocking blocks for housing projects were also observed. This paper recommends the use of the accelerated dry masonry system in housing projects and concludes that interlocking masonry is a good replacement for the conventional types of construction used in student housing projects in Nigeria.